ANALISIS KETERLAMBATAN PROSES BONGKAR MUAT KAPAL BULK CARRIER DENGAN METODE FMEA PADA PERUSAHAAN PELAYARAN DISURABAYA - Erna Amalia Nugrahini; Gaguk Suhardjito; Yugowati Praharsi (Proceeding Maritime Business Management Conference, 2023)
Shipping companies in Surabaya actively carry out coal loading and unloading on bulk carrierships with an average cargo of 39,400 MT. Based on company data, the loading and unloading process in one year experienced 19 incidents of delays. There were 8 incidents ofloading delays and 11 incidents of unloading delays. This incident resulted in reduced profitsbecause operational costs increased every day. This research aims to identify the root causesof delays in loading and unloading and provide mitigation strategies. This research uses the fishbone method to identify the root causes of loading and unloading delays and the FMEA (Failure Mode And Effect Analysis) to identify the most dominant root causes. Meanwhile, mitigation strategies are determined by interviewing company experts and journal referencesthat are in line. The results showed 12 root causes of delays consisting of 5 factors (man, machine, method, materials, and environment). The dominant root cause in the FMEA questionnaire shows waiting for the arrival of coal trucks to the warehouse, with an RPN value of 346,5. From these results, recommendations for improvementsthat can be made arecoordination with shippers, and agents, and the need to improve port facilities.